Answer:
3 and -4
Step-by-step explanation:
First, you write out each statement as an equation:
x + y = -1
2x + 4y = -10
Next, rewrite one equation so only x is on one side of the equation, and plug it into the other equation, and solve for y:
x = -y - 1
2 (-y - 1) + 4y = -10
-2y - 2 + 4y = -10
2y = -8
y = -4
Plug the found value for y into the original equation and solve for x:
x + y = -1
x - 4 = -1
x = 3
Plug both values into the second equation to check your work:
2x + 4y = -10
2(3) + 4(-4) = -10
6 - 16 = -10
-10 = -10